Middleware providing group communication facility based on multi-way synchronization for cellular phone applications - Nishigaki, K.; Yasumoto, K.; Umedu, T.; Higashino, T.; Ito, M. (24th International Conference on Distributed Computing Systems Workshops (ICDCS 2004 Workshops), 2004)
In this paper, we propose a middleware library for efficiently developing distributed cooperative applications consisting of a large number of cellular phone users. Our middleware provides (1) a dynamic group formation mechanism depending on users' locations and preferred subjects and (2) a group communication mechanism called multiway synchronization for multicasting, synchronization and mutual exclusion. Due to some restrictions in cellular phones, in our middleware, most of user programs are executed on their servers as agents. Group communication is implemented as inter-process communication on the server, and only the user-interface parts are executed on the cellular phones.